Fenomena Bunuh Diri Di Nusa Tenggara Timur: Analisis Sosial Dan Teologis Dalam Perspektif Émile Durkheim Dan John Potter: Suicide Phenomenon in East Nusa Tenggara: Social and Theological Analysis In the perspective of Émile Durkheim and John Potter - Endang Damaris Koli; Amelia Waimuri (MURAI: Jurnal Papua Teologi Konstekstual, 2026)
Suicide remains a significant global, national, and local concern, including in East Nusa Tenggara (Nusa Tenggara Timur, NTT), a region widely recognized for its strong communal and religious life. The emergence of numerous suicide cases in recent years raises important questions regarding the relationship between social conditions, religious life, and individual vulnerability to suicide. This study aims to analyze the phenomenon of suicide in NTT through a dialogue between Émile Durkheim’s theory of suicide and John Potter’s theological reflection. The study employs a qualitative approach using document analysis of eight suicide cases reported in online media between 2023 and 2026. The data were analyzed descriptively to identify recurring patterns and subsequently interpreted using Durkheim’s concepts of social integration and social regulation, as well as Potter’s reflections on stigma, grace, and pastoral care. The findings indicate that suicide cases in NTT involve various age groups and social backrounds, with male victims constituting the majority. Contributing factors include economic hardship, cultural pressures related to belis, mental health problems, interpersonal relationship issues, and other forms of social vulnerability. The dialogue between Durkheim and Potter demonstrates that suicide in NTT constitutes both a social and a theological issue. These findings highlight the importance of the church in fostering communities characterized by acceptance, accompaniment, and hope as part of pastoral responses to individuals experiencing despair.